Community participation through women’s health collectives promoted by India’s National Urban Health Mission: a realist evaluation in Chhattisgarh state - Shriyuta Abhishek; Samir Garg; Mukesh Dewangan; Ashu Sahu; Lalita Xalxo; Prabodh Nanda; Pradeep Tandan; M. Jawed Quereishi; Anand Kumar Sahu (International Journal for Equity in Health)
Abstract Background The urban poor especially women slum dwellers face health inequity including disproportionate challenges in participating meaningfully in government programmes on health and its social determinants. To allow equitable participation of the urban poor in health, India’s National Urban Health Mission has promoted women’s health collectives known as the Mahila Arogya Samitis (MAS) in urban slums since 2013. No evaluations of this important government initiative are available. Methods A realist evaluation was conducted. A sequential exploratory mixed-method approach involving the following steps was applied − 1) Developing the Initial Programme Theory on action and outcomes of MAS; 2) Testing the programme theory through quantitative and qualitative methods; and 3) Refining and consolidating the theory. Results Over three years preceding the survey, 59.1% of MAS in Chhattisgarh had taken action on healthcare related problems, 74.1% on food-security and nutrition, 60.8% on gender-based violence, 56.4% on drinking water, 70.8% on sanitation and 64.1% on social environment related issues. Around 95.3% MAS had taken action on at least one of the above six domains. The community participation through MAS was not limited to increased uptake of healthcare services but to a wider people-centred agenda on social determinants of health. The MAS were able to devise multiple strategies for identifying and solving the problems. Participatory selection of women as MAS members, autonomy in decision making, appropriate training design, regular meetings and facilitation provided to MAS by the community health workers emerged as the main enablers to their human-rights orientation and action. Their work is facilitated by the supervisory cadre under the Mitanin program under the leadership of State Health Resource Centre. The social recognition gained by women members of MAS acted as the key source of motivation to sustain their action. However, there are limitations to the actions taken by MAS. The action taken by MAS remained limited to their immediate surroundings, and they were unable to improve public accountability at the higher echelons, or bringing policy-level changes. Conclusion The MAS experience in Chhattisgarh offers an example of effective community participation of urban poor in health through a process that empowers the underprivileged women. Equitable community processes require appropriate design and need to be nurtured through capacity building and facilitation guided by a similar ethos. The government can further enhance community participation and advance equity in health by allowing collectives such as the MAS a greater say in health planning and monitoring.